Effect of one-year dextromethorphan/quinidine treatment on management of respiratory impairment in amyotrophic lateral sclerosis. (September 2021) - Sancho, Jesus; Ferrer, Santos; Burés, Enric; Luis Díaz, José; Torrecilla, Teresa; Signes-Costa, Jaime; Servera, Emilio
Abstract: Treatment with Dextromethorphan/Quinidine ( DM/Q) has demonstrated benefit on pseudobulbar affect and bulbar function in amyotrophic lateral sclerosis (ALS). The aim of this study was to assess whether DM/Q could provide long-term improvement in bulbar function and thereby prolong noninvasive respiratory management in ALS. Materials and methods: This prospective, case-cohort study, recruited ALS patients with bulbar dysfunction. Subjects included were compared with cross-matched historical controls. Cases received DM/Q (20/10 mg twice daily) during one-year follow-up; bulbar dysfunction was evaluated with the Norris scale bulbar subscore (NBS) and bulbar subscale of AlSFRS-R (ALSFRSb). Results: In total, 21 cases and 20 controls were enrolled, of whom noninvasive respiratory muscle assistance failed in 6 (28.5%) patients in the DM/Q group, compared with 4 patients (20.0%) in the control group (p = 0.645). Time from study onset to failure of respiratory muscle aids was 5.50 + 1.31 months in the DM/Q group and 5.20 + 1.15 months in the control group (p = 0.663). The adjusted OR for the effect of treatment on failure of noninvasive respiratory muscle aids was 2.12 (95%CI 0.23–33.79, p = 0.592). In the DM/Q group an impairment in scores was found in NBS (F = 19.26, p = 0.000) and ALSFRS-Rb (F = 12.71, p = 0.001) across different months of the study. Conclusion: Treatment with DM/Q in ALS is unable to prolong noninvasive respiratory management, and moreover, has no effect on long-term deterioration of bulbar function. Notwithstanding the results on bulbar function, DM/Q was found to improve pseudobulbar affect during one-year follow-up. Highlights: Treatment with DM/Q in ALS has no effect on long-term deterioration of bulbar function. Treatment with DM/Q in ALS is unable to prolong noninvasive respiratory management. Treatment with DM/Q in ALS produces an initial improvement in pseudobulbar affect and its sustained over one-year period.